PENGARUH INTERAKSI TEMAN SEBAYA TERHADAP SELF-EFFICACY SISWA - Muthia Nurlita Asri Utami; Titik Haryati (LPPM Institut Pendidikan Nusantara Global, 2023)
The prelimary field study that inspired this research found that peer connection is crucial for childer’s social and personal growth. Peer’s ability to serve as an information and comparison source outside the family is one of their most crucial roles. Everyone receives evaluations on their skills from their peers. One of the elements that affects a person’s self-efficacy is peer interaction. Peer interaction, as we all know, has a significant influence on a child’s development. Low self-efficacy in demonstating one’s one conduct can also have an impact on student learning results. This study sought to ascertain how peer interaction with students in grade XI at SMA Negeri 3 Cibinong affected their sense of self-efficacy. The researcher might make judgments based on the study. Correlational quantitative research methodology are used in this study along side as quantitive approach. 65 grade XI students from SMA Negeri 3 Cibinong made up the study’s sample through the data that was gathered using a basic random sampling procedure. Data collection techniques used questionnaire and observation methods with Likert scale measurements and conducted descriptive analysis of variables, prerequisite analysis tests, and hypothesis testing. The results of this study show that there is an influence of 18,9% with a moderate category between peer interaction on self-efficacy showing positive development, with the higher peer interaction, the higher self-efficacy of students. The results of this study were obtaines base on simple linear regression analysis, which produces a significance value of 0,000.